Understanding the biomolecular interactions involved in dimerisation of the Saccharomyces cerevisiae eukaryotic translation initiation factor 5A - Charlton, Jane Laura (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2012)
Translation initiation factor 5A (IF5A) is an essential, highly conserved protein found within all eukaryotic (eIF5A) and archaeal (aIF5A) cells. The IF5A protein is unique in that it contains the amino acid hypusine; a two-step post translational modification of a single, conserved lysine residue. Although hypusination of eIF5A is vital for eukaryotic cell viability, the primary role of the protein and its hypusine side chain remain a mystery. eIF5A, initially identified as a translation initiation factor, is not required for global protein synthesis leading to the prevailing proposal that eIF5A is purely involved in the translation of a select subset of mRNAs. Recently a number of mutational studies have focused on the conserved, hypusine-containing loop region of eIF5A where specific residues have been found to be essential for activity without affecting hypusination. It has been postulated that eIF5A exists as a dimer (40 kDa) under native conditions and that these residues may be at the interface of dimerisation. The aim of this research was therefore to conduct a mutational analysis of the loop region in support of this hypothesis. A functional analysis of the Saccharomyces cerevisiae eIF5A mutant proteins K48D, G50A, H52A and K56A revealed that these substitutions impaired growth to varying degrees in vivo with G50A and K48D mutant proteins displaying the most convincing defects. Gel filtration profiles gave unexpected results determining eIF5A mutant and wild type proteins to have a native molecular weight of 30 to 31 kDa, suggesting that the eIF5A oligomeric state may be transitory and subject to certain conditions. The inconclusive results obtained from using gel filtration studies led to an investigation into the feasibility of producing native, hypusinated peptides for future structural studies using nuclear magnetic resonance. Hypusinated and unhypusinated eIF5A were successfully separated into their domains making this a possibility. Finally, this study proposes a role for eIF5A in eukaryotic IRES-driven translation initiation.
Keywords: Proteins -- Synthesis -- Research; Saccharomyces cerevisiae -- Research; Dimers; Dimers -- Research; Eukaryotic cells -- Research; Yeast -- Research